Statistical Analysis of the Men's Indoor Hockey Final Between Indonesia and Malaysia at the 2025 Sea Games in Thailand - Tri Afdal Saputra; Masrun; Roma Irawan; Kristian Burhan (Jurnal Master Penjas & Olahraga, 2026)
This study aimed to analyze the match statistics of the men’s indoor hockey final between Indonesia and Malaysia at the 2025 SEA Games in Thailand. The research used a quantitative descriptive method with a match analysis approach. The population included all matches in the tournament, while the sample was the final match between Indonesia and Malaysia selected through total sampling. Data were collected through documentation and indirect observation by analyzing match videos and official statistical reports. The analysis covered offensive, defensive, possession, and basic technical indicators. The results showed that Malaysia dominated ball possession (52%), total shots (52), shots on target (22), and successful passes (228). However, Indonesia was more effective in converting opportunities into goals and demonstrated stronger defensive performance. In conclusion, match outcomes are influenced not only by possession dominance but also by finishing efficiency, defensive discipline, and the ability to maximize crucial opportunities.